Risk factors for cardiovascular disease in patients with non-alcoholic fatty liver disease with polymorbidity - E. V. Sevostyanova; Yu. A. Nikolaev; I. M. Mitrofanov; V. Ya. Polyakov (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the associations of the frequency and values of parameters of the main risk factors (RF) of cardiovascular diseases (CVD) and the degree of transnosological polymorbidity (PM) in patients with nonalcoholic fatty liver disease (NAFLD).Material and methods. The analysis of 3667 medical records (men, women) treated in the clinic of Research Institute of Experimental and Clinical Medicine (Novosibirsk) was carried out. Index of polymorbidity was evaluated by the number of nosological forms in accordance with the International Classification of Diseases, 10th revision (ICD-10). The following risk factors were assessed according to clinical and laboratory tests: arterial hypertension, dyslipidemia, hyperglycemia, obesity.Results. Both among men and women with increasing index of PM there was identified growth of the parameters that determine the main RF: systolic BP, diastolic BP, obesity (both in men and women), atherogenicity index (in women), glucose concentration in the blood serum (in women). Frequency of AH occurrence in persons with a high degree of PM among men was 49%, and among women — 69% higher, compared with persons with a low degree of PM. Among men, there was an increase in the incidence of AH (by 9%) and obesity (by 9%) in individuals with a high degree of PM, compared with individuals with an average degree of PM. Among women, there was an increase in the incidence of AH (by 15%), obesity (by 9%), hyperglycemia (by 11%) in persons with a high degree of PM, compared with individuals with an average degree of PM.Conclusion. There was established the role of risk factors for cardiovascular diseases, arterial hypertension mainly, in the development of polymorbidity in patients with NAFLD. The findings indicate the need for personified prevention and treatment of such patients with mandatory identification and correction of modifiable CVD RF.